(Un)finished transition. Stock of knowledge in Poland, 1924–2012 - Wallusch, Jacek (Economics and Business Review, 2015)
Technological underdevelopment of the Polish economy has been remarkablypersistent. In this paper I focus on the stock of knowledge, approximated by the10% depreciation rate of accumulated patents granted in Poland, to show its longtermstructure and to distinguish its growth phases. I test for long memory and runa Markov-switching autoregressive model. The stock of knowledge is found to be nonstationaryand mean reverting. I also discover two well-separated regimes representingslower and faster changes in the stock of knowledge. The latter regime characterisesthe years between the 1920s and mid-1950s (interrupted by the Great Depression andWorld War II), mid-1970s and the period after accessing the EU.